Case Report: Partial response to single-agent pembrolizumab in a chemotherapy-resistant metastatic pancreatic cancer patient with a high tumor mutation burden - Dai, Mengyao; Sheng, Jianpeng; Zhang, Qi; Wang, Jianxin; Fu, Qihan; Liang, Tingbo (Frontiers in Oncology, 2023)
Single-agent immune checkpoint blockade has shown no clinical benefits in pancreatic cancer. Recently programmed cell death protein 1(PD-1) antibody Pembrolizumab has been recommended as a treatment option for high Tumor Mutational Burden(TMB) solid tumor base on the data from a basket trial. However, no pancreatic cancer patients were enrolled in that trial. Whether pancreatic cancer patient with high TMB respond to PD-1 blockade as well remains unclear. Here we report a case with a partial response to single agent immunotherapy with Pembrolizumab in pancreatic cancer with high TMB after failure of several line chemotherapy. This result indicates that single-agent immunotherapy may be effective in pancreatic cancer patients with high TMB.In addition, in order to understand the basic immune state of our patients, we also analyzed the changes of immune cells in peripheral blood with Cytometry by Time-Of-Flight mass spectrometry(CyTOF) before and after with Pembrolizumab treatment.